FORMULASI GRANUL EFFERVESCENT DARI KUNYIT (Curcumae domestica) DAN ASAM JAWA (Tamarindus indica) - Arifuddin, Arisanty; Al Akram, M. Faathir; Ibrahim, Ismail (Jurnal Kefarmasian Akfarindo, 2022)
Effervescent dosage form is another way to develop attractive soft drink products and provide variety in presentation because apart from being practical, it can also give a sparkle effect or a soda-like taste and can also cover some unwanted flavors of certain ingredients. The benefits of Jamu Turmeric Tamarind have been proven empirically. Jamu Turmeric is efficacious as an antibiotic, preventing sprue, analgesic (relieves pain), antipyretic (lowers body temperature during fever), and anti-inflammatory. The purpose of this research was to formulate and evaluate the physical properties of effervescent granules from turmeric (Curcumae domestica) and tamarind (Tamarindus indica). This type of research is an experimental study conducted to formulate turmeric (Curcumae domestica) and tamarind (Tamarindus indica) in the dosage form of effervescent granules in 2 formula forms with varying acid concentrations and then evaluate their physical properties. The evaluation of granules includes water content test, angle of repose test, flow rate test, compressive density test, dispersion time test and pH test. The results showed that turmeric (Curcumae domestica) and Tamarind (Tamarindus indica) could be formulated in effervescent granule dosage form. For the flow velocity test, it was found that the flow properties of the granules were low in the two formulations